Behavioral Intention to Use E-learning: A Case Study of Apparel School Students at Chengdu Textile College in China - Fu, Hongxia; Feng, Deping (Scholar: Human Sciences, 2023)
Purpose: To create a student-centered art teaching model, e-learning is considered a new possibility to enhance the curriculum learning approach. Therefore, this research aimed to study significant factors of school of apparel students’ behavioral intention to utilize e-learning at Chengdu Textile College. The conceptual framework consists perceived ease of use, perceived usefulness, attitude, self-efficacy, performance expectancy, social influence and behavioral intention. Research design, data, and methodology: The researcher used a quantitative approach (n=488). Questionnaires were distributed to apparel school students in Chengdu Textile College. The research data was gathered through judgmental, quota and convenience sampling. The following statistical analysis was implemented through the Confirmatory Factor Analysis (CFA) and Structural Equation Model (SEM), including model fit, validity, and reliability of each construct. Results: Perceived ease of use has a significant effect on perceived usefulness and attitude. Perceived usefulness has a significant effect on attitude and behavioral intention. Furthermore, attitude, self-efficacy, performance expectancy and social influence significantly affect behavioral intention. Conclusion: The research makes recommendations for college education policymakers, college teaching quality supervision, and teacher to encourage the integration of e-learning into the fundamental teaching process and establish a modern digital and intelligent education environment in college education.